Strengthening Public Financial Management Literacy for FEB Students of Abdurachman Saleh University, Situbondo - Mirna Amirya; Pusvita Susilowati; Clarient Catherine Frederica (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2025)
Strengthening public financial management literacy is an urgent need to produce competent and highly competitive economics graduates, especially in the public sector. This article aims to measure the effectiveness of online seminars in improving students' understanding of the principles of public financial management, including fiscal policy and the preparation of government financial reports, at the Faculty of Economics and Business, Abdurachman Saleh University, Situbondo. The Kirkpatrick evaluation approach was used to assess two aspects: participant reactions and increased knowledge. The results showed that participants responded very positively to the quality of the seminar and the materials presented. In addition, the level of participant understanding of the material was relatively high, as reflected in the post-test results. These findings indicate that interactive seminar-based strategies contribute significantly to strengthening public financial literacy among economics students.